Developing Interactive Instructional Modules for Core Principles of English Language Teaching - Achmad Taqlidul Chair Fachruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This research aims to develop instuctional modul of core principles of EFL Material dealing with English Education Program curriculum at Tarbiyah and Teacher Traning Faculty of STAIN Majene. This research conducted a Research and Development (R&D) by using ADDIE Model. The subject of this research was core principles of EFL Material dealing with English Education Program curriculum of Tadris Bahasa Inggris STAIN Majene. The data of this research were collected and analyzed in proccess of development through   Model.The result of the research reveal that the the developing of core principles in ELT class was needed by student. The ADDIE Model can really help the lecturer to develope material for teaching. This research has been trying to develop Core Principle of English Languge Teaching materials in the STAIN Majene which consists of Language Components in English Language Teaching; Methods and Approaches in Language Teaching; and Evaluation and Assessment on Language Teaching which divided into some subtopics which are Language Components covering Elements of Language and Language Skills, then Methods and Approaches in Language Teaching covering The Development of Methods and Approaches of Language Teaching in the world; Kinds of Methods and Approaches in Language Teaching; and Current Methods and Approach in Language Teaching. Evaluation and Assessment on Language Teaching covering The Introduction of Measurement in Language Teaching; and Constructing Evaluation and Assessment Tools in Language Teaching.